Markus 1:4 in die Nuwe Aftikaanse Vertaling - Thom, J. C. (Hervormde teologiese studies, 1993)
Mark 1:4 in the New Afrikaans Bible Mark 1:4 is often used as an example text to illustrate the difference between traditional and newer approaches to Bible translating. The reason is that the verse contains a concatenation of nominalizations of events (i e, baptism, repentance, forgiveness and sins) which is foreign to many modern languages. In this paper the way the New Afrikaans Bible translates these words is analysed and evaluated. It is concluded that the New Afrikaans Bible’s (1983) translation of this verse has been influenced by dogmatic concerns rather than linguistic considerations.